Possibilidades e limites do programa territórios da cidadania a partir da sua realização no território região central e no município de Santa Maria/RS - Carvalho, Ananda de (2012)
Consented by the State, the territorial configuration of rural areas in Brazil is marked by uneven processes that favored restricted portion of the population, instead of family farmers, maroon people, indigenous people, rural workers and participants of the agricultural reform. However, recently, in order to ease these social disparities, the Brazilian government has granted remedial public policies directed to this issue due to the demands from popular movements. One of these policies that stand out is the implementation of the Citizenship Territories Program, whose principle is to put together different federal agencies with the state, civil and municipal administrations, in order to enhance, expand and internalize public access policies for excluded rural populations. To accomplish that, territorial and functional units were imposed, based on the territorial approach to development, which requires the valuation of multi-dimensions, multiple scales of power, social participation, as well as the association between city and countryside with the various productive sectors located in rural areas. Considering these units, one highlights the Central Region Territory / RS, whose council belongs to Santa Maria. This study aimed to identify the effects of the Citizenship Territories Program implementation, through an analysis of the examples seen in Santa Maria city. Moreover, this research discusses the use of a territorial approach as a basis to mitigate the social inequalities in Brazil in order to promote development. This analysis was organized into four components: a) the firstly, a theoretical research was carried out; b) second, an analysis of documents produced by the program; c) the third section consisted of the primary data collection through participatory field work through visitations to the entities benefitting from the program in Santa Maria city, as well as application of questionnaires for the subjects involved in this policy; d) finally, the last section of this research tried to systematize the data, by analyzing, comparing, and contrasting them in a critical and qualitative process, observing historical facts and establishing associations between theory and practice. As a result, it was found that the Citizenship Territories Program, besides both being unknown and the territorial development not being considered as the main strategy of governance in the country, it does give the opportunity to the civil society organizations to intervene in the course of state actions, besides subsidizing the democratization of access to basic rights. The case of Santa Maria city, in particular, has helped to strengthen cooperatives and rural workers union, therefore fulfilling a secondary role. Regarding the Central Region Territory / RS, it was found that it has been consolidating as a representative institution of the disposed rural areas, although there are political conflicts and realities socially and environmentally distinct.